My best book of pirates - "Harward, Barnaby" (Kingfisher London, 2005)
My Best Book of Pirates by Barnaby Harward introduces readers to the adventurous world of pirates, exploring the lives of infamous figures such as Blackbeard, Captain Kidd, and Madame Cheng. The book delves into their daring exploits, the treasures they sought, and the ships they commanded. Through engaging narratives and vivid illustrations, it provides insights into the golden age of piracy, highlighting the allure and danger of life on the high seas. This book is an excellent resource for young readers interested in history and adventure.